Analysis the Moral Value and Character Building in the " Siberu Dayang " North Sumatera's Folklore - Devia Silviana br Sitepu; Lawelin Magdalena br Kembaren; Megawati Sihombing; Yenita br Sembiring; Ira Maria Fran Lumbanbatu (Jurnal Ilmiah Wahana Pendidikan, 2022)
A character can bring someone to the succeed and unsucceed life. That’s why someone should able to create a good character in their life, especially for the children because they still have so many chances to pursue their future. Thus, this research paper wants to give some discussions about a method that wil be used to solve the problems in students’ character and moral, and that is making a learning resource for the students about moral value and characterbuilding by using folklore. This research used a research design in qualitative research method. Thus, this research would be contained of research instruments, technique of data collection, research method, data resource, and data analysis as the research design of this research, to findout the answer of this research’s problems. The researchers had found out that there were many moral values and character buildings in this folklore. The moral values were wisely govern, patient in life, cooperate, obey the rules, and fulfill the promise. The character buidings were responsible, caring each other, affectionate, never give up, and willing to sacrifice.